Desastre socioambiental de Mariana: implicações nas condições de saúde da população atingida e no processo de trabalho dos serviços de saúde - Camila da Silveira Santos (2023)
The socio-environmental disaster that occurred in Mariana, because of the collapse of the Samarco mining company's Fundão dam, devastated the communities of Bento Rodrigues and Paracatu de Baixo, causing losses and damages that can unfold over time, producing profound effects on health, in the environment, as well as in the context of life and work. With this, we seek to analyze the health-disease process and the work process in health services intended for the population affected by the socio-environmental disaster in Mariana. This is a case study conducted using a qualitative, descriptive and exploratory approach, whose setting is Mariana, where the communities directly affected by the collapse of the mining tailings dam are located. The sources of evidence used were public domain documents and interviews with health professionals and managers. The Bento Rodrigues Health Unit and the Conviver device were intentionally chosen, as they exclusively serve families who were victims of the disaster. Eleven health professionals and three managers participated in the research. The data were analyzed using the strategy of theoretical propositions in light of the theory of Social Determination of the HealthDisease Process. The results revealed the implications of the disaster on social, economic, cultural conditions and above all on the health of the affected population, with consequences related to respiratory problems and those caused by water transport or contact with toxic waste sludge, and depressive cases and other disorders, psychosocial problems that intensified the chronic suffering of the population. The implications of the disaster on the work process in services providing exclusive care to those affected highlight a (re) organization of the health system, which faced structural difficulties in both the emergency and postdisaster recovery phases. It is noteworthy that although the work process instruments used by health professionals and managers are capable of welcoming and stimulating more integrated practices, that transcend intervention only in biological bodies, they are still not capable of meeting mediated health needs of those affected, failing to promote responses to political, social and economic needs in terms of reparation, compensation and the rights of the affected population.